Association between serum zinc level and simple febrile seizures in children: a hospital-based study - Saqib, Najmus; Qazi, Mahvish (International Journal of Research in Medical Sciences, 2018)
Background: Febrile seizures are the most common cause of convulsions in children and a frequent cause of emergency hospital admissions. There are different hypothesis about neurotransmitters and trace element (such as zinc) changes in cerebrospinal fluid and serum, which can have a role in pathogenesis of febrile convulsions. Hence we want to study this association in our set up. Objectives was to study the association between serum zinc levels and febrile seizures in childern in our set up. Methods: This hospital based, prospective case control study was done in SKIMS Soura Srinagar, Kashmir (J and K), India for one-year period from August 2015 to July 2016. A total of 100 children aged 6 months to 6 years admitted in the hospital presenting with febrile seizures after fulfilling our inclusion and exclusion criteria were enrolled for the study. Informed consent was taken from their attendants and classified into 2 groups of 50 each. Patients with history of simple febrile seizures were taken as cases and those with fever without seizures as controls. A detailed history was taken, and complete physical examination was done on the patients and recorded on a precoded and pretested proforma. Blood was collected within 12 hours of admission and serum zinc levels were estimated. For statistical analysis, SPSS 17 program using t-test was employed. Chi-square test was performed to compare proportion between 2 or more discrete variables. P<0.05 was considered statistically significant. Results: Out of 100 children enrolled, male to female ratio was 1.63:1. Majority of the children were between 6 to 12 months (36%). The clinical presentation comprised of mainly non localized fevers majority of which had clinical evidence to suggest viral etiology (60%), followed by ARI (20%), ASOM (10%), UTI (6%) and bronchiolitis (4%). Mean serum zinc level in cases was 30.96±7.93ugm/dl and in controls it was 35.95±9.25ugm/dl. Serum zinc level was found significantly low in cases of simple febrile seizures as compared to controls (P<0.05). Conclusions: This study reveals that there is positive correlation between low serum zinc levels and febrile convulsions.